Should kidney allografts from old donors be allocated only to old recipients? - Süsal, Caner; Kumru, Gizem; Döhler, Bernd; Morath, Christian; Baas, Marije; Lutz, Jens; Unterrainer, Christian; Arns, Wolfgang; Aubert, Olivier; Bara, Christoph; Beiras-Fernandez, Andres; Böhmig, Georg A.; et al. (Transplant international, 2020)
In several deceased donor kidney allocation systems, organs from elderly donors are allocated primarily to elderly recipients. The Eurotransplant Senior Program (ESP) was implemented in 1999, and since then, especially in Europe, the use of organs from elderly donors has steadily increased. The proportion of ≥60-year-old donors reported to the Collaborative Transplant Study (CTS) by European centers has doubled, from 21% in 2000-2001 to 42% in 2016-2017. Therefore, in the era of organ shortage it is a matter of debate whether kidney organs from elderly donors should only be allocated to elderly recipients or whether <65-year-old recipients can also benefit from these generally as “marginal” categorized organs. To discuss this issue, a European Consensus Meeting was organized by the CTS on April 12, 2018, in Heidelberg, in which 36 experts participated. Based on available evidence, it was unanimously concluded that kidney organs from 65- to 74-year-old donors can also be allocated to 55- to 64-year-old recipients, especially if these organs are from donors with no history of hypertension, no increased creatinine, no cerebrovascular death, and no other reasons for defining a marginal donor, such as diabetes or cancer.
Gesehen am 16.08.2021